Inflammasomes as regulators of mechano-immunity - Bezbradica, JS; Bryant, CE (EMBO Press, 2023)
Mechano-immunity, the intersection between cellular or tissue mechanics and immune cell function, is emerging as an important factor in many inflammatory diseases. Mechano-sensing defines how cells detect mechanical changes in their environment. Mechano-response defines how cells adapt to such changes, e.g. form synapses, signal or migrate. Inflammasomes are intracellular immune sensors that detect changes in tissue and cell homoeostasis during infection or injury. We and others recently found that mechano-sensing of tissue topology (swollen tissue), topography (presence and distribution of foreign solid implant) or biomechanics (stiffness), alters inflammasome activity. Once activated, inflammasomes induce the secretion of inflammatory cytokines, but also change cellular mechanical properties, which influence how cells move, change their shape, and interact with other cells. When overactive, inflammasomes lead to chronic inflammation. This clearly places inflammasomes as important players in mechano-immunity. Here, we discuss a model whereby inflammasomes integrate pathogen- and tissue-injury signals, with changes in tissue mechanics, to shape the downstream inflammatory responses and allow cell and tissue mechano-adaptation. We will review the emerging evidence that supports this model.